The Impact of Social Media on Mental Health in the United States: The Role of Algorithms - Behravan, Ghazal; Manger, Lovejeet; Rassam, Salwan (McMaster University Journal of Public Health, 2026)
Social media has revolutionized how people think, connect, behave, and interact with one another. In this paper, we take a deeper dive into Social Media Addiction (SMA), Problematic Social Media Use (PSMU), and the role that engaging algorithms and an attention-driven economy play in the development of these phenomena. We also look at current American policies on this matter, and conclude with evidence-based policy changes and calls to action.